Phase-transition mechanism of vanadium titanomagnetite sintering with varing TiO2 ratio from 2.00 wt% to 6.00 wt% - Peng Hu; Junjie Zeng; Yuxiao Xue; Rui Wang; Ningyu Zhang; Mingrui Yang; Xuewei Lv (Journal of Materials Research and Technology)
High-Ti vanadium titanomagnetite (VTM) is much harder to be effectively utilized for sintering due to its higher TiO2 ratio. In this paper, the phase-transition mechanism of VTM sintering at different TiO2 ratios was systematically revealed by the analysis of theoretical thermodynamics, liquid phase formation characteristics and sinter compact mineralogy. Combined with mini-sintering tests, the effect of TiO2 ratio on the compressive strength and reducibility of VTM sinter compacts was verified and the appropriate TiO2 ratio was recommended. The results indicate that the gibbs free energy change of the reaction of TiO2 with CaO is much lower than that of Fe2O3 with CaO, which means perovskite (CaTiO3) is preferentially formed compared with silico-ferrite of calcium and aluminum (SFCA). Increasing TiO2 ratio improves liquid phase formation temperature and deteriorates liquid phase fluidity. Furthermore, SFCA amount is reduced and perovskite amount is increased, particularly at TiO2 ratio exceeding 4.00 wt%. Acicular and dendritic SFCA with higher strength and better reducibility is gradually transformed into tabular SFCA with relatively lower strength and poorer reducibility. The pore structure of sinter compacts is gradually developed. Thus, the compressive strength and reducibility index of sinter compacts are greatly reduced from 1734 N to 79.6 wt% to 1130 N and 67.9 wt% with TiO2 ratio increased from 2.00 wt% to 6.00 wt%. In addition, the compressive strength and reducibility index of sinter compacts are relatively better with TiO2 ratio no more than 4.00 wt%, which are consistently higher than 1400 N and 75 wt%.